ANALISIS PERAN CUSTOMER SERVICE DALAM MENINGKATKAN PELAYANAN DAN KAITANNYA DENGAN KINERJA BMT - Novellyn Experance; Jon Kenedi (BORJUIS: JURNAL OF ECONOMY, 2024)
This thesis is entitled. "Analysis of the Position of Customer Service in Improving Services and its Relation to BMT Capabilities (Research at BMT Al Fattah Solok City)" Compiled by Novellyn Experance NIM 3320360 Sharia Banking, Faculty of Economics and Islamic Business, State Islamic University (UIN) Sjech M . Djamil Djambek Bukittinggi Class of 2020. Supervisor Jon Kenedi, SE., Millim This research is motivated by the position of Customer Service in improving BMT services and capabilities. This research aims to identify the position of Customer Service in improving services and capabilities for BMT Navy (AL) Fattah Solok City customers. The type of research used is quantitative research. The analysis procedure used consists of 3 parts, namely instrument experiments (validity and reliability experiments), classical assumption experiments (normality experiments) and assumption experiments (simple linear regression analysis, relationship coefficient experiments, confirmation coefficient experiments (r2), and t experiments). The results of this research were processed using SPSS 24 and can be observed from the experimental results t which prove that Service elasticity ( ( r2) it is known that the elastic effect of Services